2017
DOI: 10.1016/j.firesaf.2017.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous combustion coal parameters for the Crossing-Point Temperature (CPT) method in a Temperature–Programmed System (TPS)

Abstract: Coal fires originate from coal spontaneous combustion caused by oxidation starting even at low temperatures. In order to evaluate the heating and oxidation of coal placed inside a container, a Temperature-Programmed System (TPS) is used under various flow and oxidation conditions for temperatures ranging from 40 to 250 o C. As the coal samples are heated in the container within the TPS, the concentration histories of the gaseous products are measured as well as the temperature history at the center of the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…With the increase in mineral content (indicated by increasing ash content), it has been shown that the crossing point of coal temperature increases (CPT), which is used to evaluate the spontaneous combustion of coal. The Crossing-point Temperature (CPT) is the temperature (temperature and corresponding time) at which the increasing coal temperature is equal to the increasing oven temperature within a Temperature-Programmed System (TPS) [ 18 ]. These results suggest that Bamboo with 6.5% ash content should be the most subject to spontaneous combustion, while Qp should be the least affected (0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…With the increase in mineral content (indicated by increasing ash content), it has been shown that the crossing point of coal temperature increases (CPT), which is used to evaluate the spontaneous combustion of coal. The Crossing-point Temperature (CPT) is the temperature (temperature and corresponding time) at which the increasing coal temperature is equal to the increasing oven temperature within a Temperature-Programmed System (TPS) [ 18 ]. These results suggest that Bamboo with 6.5% ash content should be the most subject to spontaneous combustion, while Qp should be the least affected (0.5%).…”
Section: Resultsmentioning
confidence: 99%
“…They showed that under an initial temperature of 70 ℃, changing the ventilation rate has no evident effect on CO production. Xu et al 18 tested the spontaneous combustion characteristics of bituminous coal under different oxygen concentrations. As the oxygen concentration decreased, the temperature corresponding to four stages slightly increased.…”
Section: Introductionmentioning
confidence: 99%
“…To study the mechanism of coal spontaneous combustion, . the effects of coal ash, moisture, sulfur content, particle size, volatile matter, and porosity on coal spontaneous combustion are analyzed (Arisoy and Beamish 2015;Li et al 2018), the characteristics, such as activation energy, oxygen consumption rate, and exothermic strength, of coal spontaneous combustion are tested (Xu et al 2017;Oren and Sensogut 2018;Zhang et al 2018;Zhong et al 2019), the influence of external environment on coal spontaneous combustion is revealed by changing oxygen concentration, gas concentration, nitrogen concentration, humidity, and other parameters in wind flows (Ma et al 2017;. Studies show that risks associated with coal spontaneous combustion in goafs are not only related with coal spontaneous combustion tendency but also with coal external environments (Liu and Zhou 2010;Li et al 2016;Kong et al 2017).…”
Section: Introductionmentioning
confidence: 99%